AN ANALYSIS OF LEARNING ENGLISH DIFFICULTY OF WRITING NARRATIVE SKILLS USING ONLINE MEDIA OF SMA NEGERI 4 BINJAI ACADEMIC YEAR 2021/2022 DURING COVID-19 PERIOD - juliantina sebayang; Dewi Rulia Sitepu; Ratna Sari Dadari (STKIP Budidaya Binjai, 2022)
The aim of this research was to analysis of learning English difficult on writing narrative skills using online media of SMA Negeri 4 Binjai in academic year 2021/2022 during Covid – 19 period. The sample of this research was 74 students were chosen as the sample randomly. The method of this research was qualitative research. This research used observation, interview, questionnaire and documentation as technique of collecting data. The data collected by using questionnaire from Google Form that share from WhatsApp group and interviewed 5 students with the same questions about learning English difficulty using online media and the material about writing narrative text. The analysis data of the research using percentative formulation. The result of research at SMA Negeri 4 Binjai are the importance for teacher to evaluated learning method both offline or online so the students can understand the learning material well in accordance with the expectations of each individual.